Kebebasan Beragama dalam Literatur Tafsir At-Taḥrīr wa At-Tanwīr Karya Tāhir Ibn Âsyūr - Lufaefi (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2023)
Religious freedom is a study and concept that is still being debated. In general, there are two opposing groups in viewing the concept of religious freedom, namely the literal group and the extreme group. The first group believes that religious freedom is a concept opposed by Islam. Freedom of religion is the same as the concept of apostasy whose perpetrators must be killed. Meanwhile, according to extreme groups, freedom of religion is a necessity, which is affirmed by religion. This study raises the view of Tāhir Ibn Asyūr in the interpretation of At-Taḥīr wa At-Tanwīr by using qualitative research methods. The analysis used is the analysis of hermeneutics and maqāṡhid Al-Qur'an. This study concludes that religious freedom in the view of 'Asyr is a concept that is indeed affirmed by religion, but with certain conditions, namely people who change religion because of the desire of the heart, not to play games, do not insult previous religions, and maintain tolerance among religious believers.